Evaluation of the central and peripheral effects of doxepin on carrageenan-induced inflammatory paw edema in rat - Mohsen Zabihi; Valiollah Hajhashemi; Mohsen Minaiyan; Ardeshir Talebi (Wolters Kluwer Medknow Publications, 2017)
The anti-inflammatory effects of anti-depressants have been demonstrated recently. Doxepin, a tricyclic antidepressant drug (TCA), has some special properties in comparison with the other members of its family. It has some H 1 , H 2 , alpha-1 adrenergic and muscarinic receptor blocking effects. It revealed also anti-nociceptive and relatively potent sedative effects. This study was aimed to evaluate its possible anti-inflammatory effect in a well-established animal model. Male Wistar rats weighing 200-250 g were used in carrageenan-induced inflammatory paw edema model. The test and control drugs were injected by intraperitoneal (i.p.) and intracerebral (i.c.v.) routes. The anti-inflammatory activity of doxepin (15, 30 and 60 mg/kg, i.p. and 50 and 100 μg/rat, i.c.v.) and the reference drug, dexamethasone (2 mg/kg, i.p.) were evaluated by determination and comparison of some involved biological markers including the paw volume, cytokine levels (interleukin 6 (IL-6), IL-1β, tumor necrosis factor α (TNFα, myeloperoxidase (MPO) activity and histopathological parameters. All i.p. doses of doxepin showed significant anti-inflammatory effect. It also significantly reduced MPO activity and cytokine levels and improved histopathologic parameters of carrageenan-injected paw tissues. I.c.v. administration of the drug did not show any significant reduction of carrageenan-induced paw edema. Although the exact mechanism of the anti-inflammatory effect of doxepin is not clear, it seems that reduced leukocyte migration and pro-inflammatory cytokines play important role in its anti-inflammatory effect. Also central sites are not involved in the anti-inflammatory effect of the drug.